Comparison of stereopsis thresholds measured with conventional methods and a new eye tracking method. - Lu Liu; Bo Yu; Lingxian Xu; Shiyi Wang; Lingzhi Zhao; Huang Wu (PLoS ONE, 2023)
Purpose Stereopsis is the ability to perceive depth using the slightly different views from two eyes. This study aims to conduct innovative stereopsis tests using the objective data outputted by eye tracking technology. Methods A laptop and an eye tracker were used to establish the test system. Anaglyphic glasses were employed to execute the stereopsis assessment. The test symbol employed was devised to emulate the quantitative measurement component of the Random Dot 3 Stereo Acuity Test. Sub-pixel technology was used to increase the disparity accuracy of test pages. The tested disparities were: 160″, 100″, 63″, 50″, 40″, 32″, 25″, 20″, 16″, and 12.5″. The test was conducted at a distance of 0.65m. Conventional and eye tracking stereopsis assessments were conducted on 120 subjects. Wilcoxon signed-rank test was used to test the difference, while the Bland-Altman method was used to test the consistency between the two methods. Results The Wilcoxon signed-rank test showed no significant difference between conventional and eye tracking thresholds of stereopsis (Z = -1.497, P = 0.134). There was a high level of agreement between the two methods using Bland- Altman statistical analysis (The 95 per cent limits of agreement were -0.40 to 0.47 log arcsec). Conclusions Stereoacuity can be evaluated utilizing an innovative stereopsis measurement system grounded in eye tracking technology.